INFLUENCE OF TRANEXAMIC ACID ON HEMORRHAGE AT THE REVISION HIP REPLACEMENT SURGERY - A. M. Ageenko; A. V. Zhukov; T. I. Pospelova; G. G. Guschevarova; S. A. Mikheeva (Acta Biomedica Scientifica, 2012)
The article describes the results of investigation of the influence of tranexamic acid, on hemostasis system, at the revision hip replacement surgery. Correlation of changes in hemostasis system, and hemorrhage in intra-and postoperative periods, frequency of hemotransfusion, at the stages of the operation and in postoperative period, were evaluated. Use of tranexamic acid, at the revision hip replacement surgeries reduces perioperative hemorrhage.